Sistema automatizado para ensaio de inversores fotovoltaicos conectados à rede em acordo com normatização brasileira - Figueira, Henrique Horst (2016)
This document aims to develop an automated test platform for grid-connected photovoltaic inverters. Therefore, it was conducted a study of European, North American and Brazilian standards related in order to compare the Brazilian standard with respect to the others. A comparison between them with respect to the operating limits is presented. Further, the restrictions are evaluated for each equipment used in the testing of PV inverters certification: CA emulator source emulator PV supply, power analyzer, oscilloscope and flickermeter. Finally, it was developed a software for automation of tests, which is applied for supporting the configuration sources processes, acquisition measures and test report generation. This software is evaluated by obtaining experimental tests, whose results are compared with equivalent obtained through non-automated tests, enabling the validation of the system.